ANALISIS KELAYAKAN OBJEK WISATA HUTAN MANGROVE GURAPING DI KECAMATAN OBA UTARA, KOTA TIDORE KEPULAUAN, PROVINSI MALUKU UTARA - Latupapua, Yosevita Th; Soselisa, Fanny (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2022)
Guraping mangrove tourism object is located in North Oba District, Tidore Island City. An area that has an important role in supporting physical, chemical, biological, and social functions. However, with the increase in population, it will certainly affect the ecological sustainability of the mangrove itself due to logging actions carried out by the community. Therefore, in supporting the preservation of mangroves in the village of Guraping, the mangrove area is designated as a protected area and a natural tourist attraction. To support the management of natural tourism in the mangrove area, it is necessary to be supported by information on the feasibility of the Guraping mangrove tourism object. The purpose of this study is to analyze the feasibility of the Guraping mangrove tourism object for natural tourism activities. The research was conducted in July 2022. The research method used is descriptive quantitatif method. Determination of sample points using the purposive sample method, sampling was carried out at 3 observation stations, data analysis using quantitative analysis of mangrove feasibility. The results showed that the mangroves of the Guraping tourism area had an IKW value of 72 with the S2 category ("appropriate") to be developed as a tourist attraction. ABSTRAK Objek wisata mangrove Guraping yang berada di Kecamatan Oba Utara kota Tidore kepulauan. Merupakan kawasan yang memiliki peran penting dalam menunjang fungsi fisik, kimia, biologi, dan sosial. Oleh sebab itu dalam menunjang kelestarian mangrove di desa Guraping kawasan mangrove ditetapkan sebagai kawasan lindung dan objek wisata alam. Untuk menunjang pengelolaan wisata alam dalam kawasan mangrove, perlu didukung dengan informasi kelayakan kawasan objek wisata mangrove Guraping. Adapun tujuan dari penelitian ini adalah menganalisis kelayakan objek wisata mangrove Guraping untuk aktifitas wisata alam. Penelitian di lakukan pada bulan Juli 2022. Metode penelitian yang digunakan yaitu metode deskriptif kuantitatif. Penentuan titik sampel menggunakan metode purposive sample, pengambilan sampel dilakukan di 3 stasiun pengamatan, analisis data menggunakan analisis kelayakan mangrove untuk wisata. Hasil penelitian menunjukkan bahwa mangrove kawasan wisata Guraping memiliki nilai IKW 72 dengan kategori S1 (“sangat sesuai”) untuk dikembangkan sebagai objek daya tarik wisata. Kata kunci : Ekowisata, mangrove, hutan Guraping, objek wisata, Maluku Utara